UPAYA GURU DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI PAUD ROSELLA PONTIANAK UTARA - Asmiati, Syarifah; Chiar, M.; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractCreativity is an important thing that children have that needs to be improved. Through a variety of learning media used by teachers, optimizing all aspects of children's creativity development. This then makes researchers want to examine the efforts of teachers in developing the creativity of children aged 5-6 years in PAUD Rosella North Pontianak. The questions in this study are what the teacher does, how and how to evaluate learning in developing original creativity in children aged 5-6 years in PAUD Rosella North Pontianak. The method used in this study was descriptive with a qualitative approach. The location of the study was conducted at Rosella PAUD North Pontianak. Techniques for collecting data used interview techniques, observation and documentation. The results of this study indicated that the efforts of teachers in developing creativity in children aged 5-6 years in RosellaPAUD North Pontianak, teachers make plans for implementing daily learning (RPPH). In making plans for implementing learning, the teacher determined the activities to be carried out and prepares the media / learning resources needed. The teacher also guides and motivates children in conducting experiments to develop creativity in children aged 5-6 years in PAUD Rosella, North Pontianak.Keywords: Children aged 5-6 years, creativity, teacher's effortsÂ